Instilling Religious Character Values, Independence and Responsibility in Early Childhood at Foster Ki Hajar Dewantara Kindergarten - Rosmalia, Rosmalia; A. Samina, Nurintan; Hadisa, Hadisa; Dewi Arlusi , Rosalina (PT Literasi Nusantara Publisher, 2022)
The early age period is the period that underlies the next human life. This period is usually called the golden age, namely the golden age of children. It is very important to instil character education from an early age. Because this will carry over into adulthood. There are 18-character education values ​​to be instilled in early childhood. In the research we conducted at Pembina Ki Hajar Dewantara Public Kindergarten, there were several prominent characters that were instilled in early childhood at the school including religious values, independence values, and responsibility values. Based on the results of research conducted at Ki Hajar Dewantara TK Negeri Pembina Ki Hajar Dewantara which has been carried out by researchers, it can be concluded that there are 3-character values that are more prominent or dominantly applied in TK Pembina Ki Hajar Dewantara namely religious values, independence, and responsibility.